無家之寶 = homeless treasures. - Li, Ivy Kexin. (2011)
The title of my Final Year Project is 無家之寶 （Translated as “Homeless Treasures), which a pun based on a Chinese saying“無價之寶”(Translated as “Priceless Treasures”); to demonstrate the irony of the homeless stray cats and dogs in Singapore. I have been active in the local animal welfare scene since five years ago. What moved me to identify and feel for them is my first bout of psychological break down followed by several diagnoses over a span of years. From my fear of leaving my house to the process of being able to be out in the public, that is, the void deck, I discovered that I could find solace in spending time with the stray cats and made acquaintances with stray-feeders, who are the so-called ‘cat ladies’. Delving into the psyche of animal rescuers, and having animals as confidantes, I began to see from a new perspective of life through my interpretation of my relationship with the animals and how caregivers interact with their strays.I spent the past year living in a local animal boarding house and shelter, finding an emotional and psychological ‘home’ with the animals.